Penyediaan Karang Memadu bagi Warga yang Berpoligami di Desa Adat Penglipuran Kabupaten Bangli - Kharisma Nanda Sattwika; Diah Gayatri Sudibya; Ni Made Puspasutari Ujianti (Fakultas Hukum, Universitas Warmadewa, 2020)
The authority of the customary law community covers various fields of human life, including in the field of marriage. In the field of marriage, customary law community unity regulates its own marriage patterns as applied by customary law community unit in Penglipuran Adat Village, Bangli Regency, there are customary rules that forbid its citizens from polygamy by providing a place called coral combined for traditional village manners that do polygamy. The study examines two problem formulations namely how the marriage system in the Penglipuran traditional village, and what the function of the reefs is to integrate polygamy marriage in the Penglipuran traditional village. The research method used in this study is empirical legal research with the sociology of law approach. The results showed that the Penglipuran Indigenous Village implemented a Monogamy marriage system that had long been designed before it was published in Law Number 1 of 1974 concerning Marriage. Related to the function of coral reefs is to prevent polygamy marriages. The main goal is to give a woman's happiness as a wife. While the influence of the supply of coral blends is very effective because until now there are no residents who occupy the coral blends because there are no Penglipuran people who do polygamy. With this research it is expected that the Penglipuran Indigenous village should maintain and preserve the values ​​of its local wisdom, because the Indigenous Village of Penglipuran is a well-known tourist destination. In addition, the government should always provide guidance to village officers to maintain the preservation of cultural values.